Janus Gold Nanoplatform for Synergetic Chemoradiotherapy and Computed Tomography Imaging of Hepatocellular Carcinoma - Wang, Zheng; Shao, Dan; Chang, Zhimin; Lu, Mengmeng; Wang, Yingshuai; Yue, Juan; Yang, Dian; Li, Mingqiang; Xu, Qiaobing; Dong, Wen-fei (ACS nano, 2017)
There is a pressing need to develop nanoplatforms that integrate multimodal therapeutics to improve treatment responses and prolong the survival of patients with unresectable hepatocellular carcinoma (HCC). Mesoporous silica-coated gold nanomaterials have emerged as a novel multifunctional platform combining tunable surface plasmon resonance and mesoporous properties that exhibit multimodality properties in cancer theranostics. However, their reduced radiation-absorption efficiency and limited surface area hinder their further radiochemotherapeutic applications. To address these issues, we designed Janus-structured gold-mesoporous silica nanoparticles using a modified sol–gel method. This multifunctional theranostic nanoplatform was subsequently modified via the conjugation of folic acid for enhanced HCC targeting and internalization. The loaded anticancer agent doxorubicin can be released from the mesopores in a pH-responsive manner, facilitating selective and safe chemotherapy. Additionally, the combination of chemotherapy and radiotherapy induced synergistic anticancer effects in vitro and exhibited remarkable inhibition of tumor growth in vivo along with significantly reduced systematic toxicity. Additionally, the Janus NPs acted as targeted computed tomography (CT)-imaging agents for HCC diagnosis. Given their better performance in chemoradiotherapy and CT imaging as compared with that of their core–shell counterparts, this new nanoplatform designed with dual functionalities provides a promising strategy for unresectable HCC theranostics.